The enterprise is the actual place for the entrepreneurial function in economic theory - Eduard Braun (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2016)
The enterprise is an historical phenomenon specific to capitalism. It is a fictional agent created by accounting and sanctioned by law. It is based on capital and its purpose is to yield monetary profit. Within the framework of the market economy, production is organized according to the decisions and actions of the aggregate of these artificially created agents. This paper demonstrates that the "entrepreneur" as used in economic theory is nothing but a personification of the enterprise. In the most renowned economic theories of entrepreneurship, the entrepreneurs are supposed to be in possession of the resources they employ. Yet the functions which these theories ascribe to the entrepreneurs implicitly presuppose that the latter not only possess resources, but that they actually own them. Without capital, which grants the power to obtain property rights in resources, entrepreneurs would not be able to bear the losses that come along with the entrepreneurial functions. The theories violate their own definitions by changing their object from a "pure" and property-less entrepreneur to a capital-owning agent. These theories can be reinterpreted, therefore, as applying not to the pure entrepreneur but to the capital-based enterprise. They then become theories of how and according to which principles enterprises organize the production process in capitalism. In contrast to the theoretical construct of the entrepreneur, enterprises are even present, though only implicitly, in neoclassical equilibrium analysis. They provide the setting of optimal decision making and therein constitute the tacit rationale of the notorious assumptions of complete foresight and perfect rationality.
Keywords: D50; L26; P12; 330; Theory of the entrepreneur; Capitalist enterprises; Equilibrium